The effectiveness of rehabilitation in vulvovaginal atrophy - D. М. Ampilogova; А. G. Solopova; D. V. Blinov; А. Е. Ivanov; S. V. Khlopkova; G. К. Bykovshchenko (IRBIS LLC, 2024)
Objective: to evaluate the effectiveness and safety of rehabilitation programmes in patients with vulvovaginal atrophy (VVA).Material and methods. The study involved 350 patients with VVA in surgical (n=140) and natural (n=140) menopause, the control group included 70 women without VVA. Patients with VVA were distributed into groups receiving complex "active" rehabilitation (surgical menopause: group 1A, natural menopause: group 2A) and "passive" rehabilitation (surgical menopause: group 1B, natural menopause: group 2B). Body mass index (BMI), vaginal pH, carbohydrate profile with calculation of insulin resistance index (HOMA-IR), inflammatory markers leptin, interleukin-6, tumour necrosis factor alpha, serum magnesium, and safety profile with evaluation of adverse events related to rehabilitation measures were assessed over 24 months.Results. BMI decreased significantly in groups 1A and 2A. Vaginal pH at 1-year follow-up decreased in groups 1A and 2A, but increased in groups 2A and 2B. BMI was higher than normal in all patients with VVA, as well as in the control group, demonstrating preobesity (groups 1A, 2A, control group) or first-degree obesity (initially in group 1B and throughout follow-up in group 2B). HOMA-IR initially reflected postoperative insulin resistance in groups 1A and 2A, but in those receiving complex "active" rehabilitation the dynamics of its reduction was the most pronounced. The concentration of inflammatory markers was initially increased compared to the control group and decreased over time in groups 1A and 1B, but only leptin levels reached the control group values by the end of the study. Serum concentration of magnesium levels was 0.71±0.12 mmol/l in group 1A, 0.71±0.10 mmol/l in group 2A, 0.76±0.08 mmol/l in group 1B, 0.72±0.17 mmol/l in group 2B (magnesium deficiency). When organic magnesium salts in combination with pyridoxine were supplemented in groups 1A and 1B, serum magnesium levels were restored to normal from the 3rd month of follow-up. No adverse events were registered.Conclusion. The personalised programme of complex "active" rehabilitation in patients with VVA is more effective than "passive" rehabilitation with comparable safety profile. Its implementation into routine practice will contribute to the improvement of the quality of health care for such patients.